Public expenses in education and youth unemployment rates: A vector error correction model approach - Nevila Mehmetaj; Nevila Xhindi (Economies, 2022)
In the last decade, much of the attention of public expenditures in education has been focused on improving the offer to the labor market to minimize unemployment rates among young people. Since education directly affects human capital, investing in higher education is considered a benefit to future employment. Therefore, it is the purpose of this paper to investigate whether the government-allocated share of funds to total public expenditures in education affects the unemployment rates of youth in Albania. A quantitative analysis of total public expenses in education and of the country's economic growth rates is used to investigate their effects on youth unemployment rates in the country. This is followed by another deeper investigation of public expenses in higher education and the country's economic growth rates analysis on the youth unemployment rates of tertiary education graduates in Albania. Time series data are used in a set of econometric analyses such as the Augmented Dickey-Fuller test, Johansen test, and vector error correction (VEC) model to test for short-run dynamics and long-run causalities among the variables. The study results reveal that there is a short-term causality between the real economic growth rate and the youth unemployment rate, while there is a long-term causality between total public expenditures in education and the youth unemployment rate. If total public expenditures in education increase by 1%, the youth unemployment rate would decrease by 10.81%. Similarly, but not so strong, there is a long-term causality between public expenditures in higher education and the graduated youth unemployment rate. If public expenditures in higher education increase by 1%, the graduated youth unemployment rate would decrease by 5.85%. The speed of adjustment from the short-run to long-run equilibrium, in a quarter time, of the youth unemployment rate is 22%, while of the graduated youth unemployment rate is 53%-showing a faster convergence.
Keywords: O01; O011; O015; 330; economic growth rates; public education expenses; youth unemployment rates